2013
DOI: 10.1016/j.drugalcdep.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine related brain activity: The influence of smoking history and blood nicotine levels, an exploratory study

Abstract: OBJECTIVE In this study, we sought to explore brain activity in nicotine-dependent men in response to acute intravenous nicotine using pharmacological magnetic resonance imaging (phMRI). METHODS phMRI was used to evaluate brain activity in response to 1.5 mg/70 kg intravenous nicotine or saline. The nicotine and saline were administered on different visits. The time courses of individual subjects’ nicotine levels were used as regressors to assess neural activity relating to the infusions. The influence of Sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…First, using blood oxygen level‐dependent fMRI, alterations of resting‐state functional connectivity in heavy smokers might be a result of vascular and neuroadaptations involved in chronic cigarette exposure (Yamamoto et al . ), thus further study should be performed to validate our findings. Second, alcohol consumption in the subjects was not assessed quantitatively using tools such as alcohol use disorders identification test.…”
Section: Discussionmentioning
confidence: 59%
“…First, using blood oxygen level‐dependent fMRI, alterations of resting‐state functional connectivity in heavy smokers might be a result of vascular and neuroadaptations involved in chronic cigarette exposure (Yamamoto et al . ), thus further study should be performed to validate our findings. Second, alcohol consumption in the subjects was not assessed quantitatively using tools such as alcohol use disorders identification test.…”
Section: Discussionmentioning
confidence: 59%
“…Nicotine (absorbed into the blood through the vapour produced by the ENDS) is likely to only enter the brain between 5 and 20 seconds after each inhalation 11 , and modelling this effect within a conventional fMRI design would be difficult, since the timing of the nicotine ‘hit’ after each trial is somewhat uncertain. There is a large literature on nicotine and its pure pharmacological effects are relatively well understood 6 , 7 . The current data stand as complementary to this literature, and provide a visualisation of brain processes related to the consumption of nicotine in a relatively naturalistic manner.…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral reduction in right hemisphere structures was rarely mentioned but has been reported for the olfactory gyrus and anterior cingulate cortex [ 25 ] and the cerebellum [ 27 ]. A study of brain activation following nicotine infusion showed increased activity bilaterally in several structures but also decreased activity in some structures including the left hippocampus, which was the only unilateral structure mentioned [ 29 ]. Overall, nicotine seems to affect the left hemisphere structures more than the right.…”
Section: Introductionmentioning
confidence: 99%